EFEKTIVITAS KOMPRES HANGAT JAHE MERAH 30 MENIT DAN 20 MENIT PADA DISMINORE REMAJA PUTRI DI KLINIK BKM TANGERANG 2022 - Wahyuni, Diana Rifka Yulia (Politeknik Tiara Bunda, 2022)
Dysmenorrhea is the most frequently complained about by women. Dysmenorrhea is generally not dangerous but often interferes with the activities of people who experience it. Young women who experience dysmenorrhea and are participating in learning activities can have an impact on their learning activities because they become disrupted, disinterested, have decreased concentration, or even have difficulty concentrating, so that the material presented during learning is not well accepted. The purpose of this study was to determine the effect of giving red ginger on reducing dysmenorrheal pain in adolescents at Klinik BKM Tangerang. The research design used was a quasi-experimental study with a group pretest and posttest design. The tools or instruments used in this study were standard operating procedures (SOP) for making red ginger drinks and NRS (Numeric Rating Score) observation sheets. The results of the study found that of the 63 respondents at Klinik BKM Tangerang before being given red ginger, those who were on a pain scale of 0 (no pain) were 20.6%, mild pain was 23.8%, and moderate pain was as many as 34 respondents. 9%, and severe pain as much as 17.5%. So it can be concluded that most of the respondents experienced a moderate pain scale of 34.9% before being given red ginger and the dysmenorrhea pain scale for students of Klinik BKM Tangerang after being given red ginger, which are on a pain scale of 0 (no pain) 74.6% and have mild pain as much as 7.9% of respondents. The conclusion is that giving red ginger is effective in reducing dysmenorrhea pain. With the test value of the Wilcoxon signed Rank Test, the results obtained are Asymp.sig (2-tailed) 0.000 < α = 0.05.